Institutional sustainability of Malaysian homestays : government perspective / Ann Selvaranee Balasingam…[et al.] - BojeI, Jamil; Awang, Khairil Wahidin; Mohd Radzi, Salleh (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2017)
Institutional sustainability issues within the Malaysian homestays product over the last 30 years include lack of governance and leadership issues. This research intends to test the relationship between three institutional sustainability indicators namely; flexibility, self-organization, and power-sharing against homestay sustainability from the government perspective. The concept of homestay sustainability and stakeholder theory underpins this study. Survey questionnaires were collected from 115 government officials to fill out based on a five-point Likert scale. The sampling strategy is convenience sampling, and the data was analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) approach. The findings of the study confirm the significant relationship between flexibility, self-organization and powersharing and homestay sustainability